Laboratory experiments to characterize cation-exchanging tracer behavior for fracture surface area estimation at Newberry Crater, OR. (January 2015) - Dean, Cynthia; Reimus, Paul; Oates, Jeffrey; Rose, Peter; Newell, Dennis; Petty, Susan
Highlights: Li + and Cs + cation exchange parameters were estimated for an EGS demonstration site. Data aid interpretation of single-well tests to interrogate fracture surface area. Li + transport shows strong temperature dependence. Cs + transport indicates weaker temperature dependence. Abstract: A series of column transport experiments ranging from 25 °C to 275 °C, as well as batch sorption experiments at 25 °C, were conducted to estimate cation exchange parameters for lithium and cesium at the Newberry Crater Enhanced Geothermal System demonstration site. The experiments were designed to facilitate interpretation of single-well field tracer tests to interrogate fracture surface area. Lithium column transport from 125 °C to 275 °C showed a strong temperature dependence, with much greater cation exchange at higher temperatures than in 25 °C experiments. Cesium column transport at 225 °C indicated a weaker temperature dependence, and unlike Li +, its exchange decreased at higher temperatures.